1998
DOI: 10.1093/oxfordjournals.aje.a009675
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cryptosporidium parvum Infection in Peruvian Children: Growth Faltering and Subsequent Catch-up Growth

Abstract: The authors conducted a 2-year (1989-1991) community-based longitudinal study in a shantytown in Lima, Peru, to examine the effect of Cryptosporidium parvum infection on child growth during the year following the onset of infection. A cohort of children, aged 0-3 months at recruitment, was followed monthly for anthropometrics, weekly for stool samples, and daily for diarrheal status. Data from 185 children in the cohort permitted a comparison of growth in C. parvum-infected and noninfected children. The analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
204
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(222 citation statements)
references
References 24 publications
15
204
1
2
Order By: Relevance
“…Nevertheless, serologic data suggest that even intensive stool surveillance may miss a substantial proportion of cryptosporidiosis episodes (20). Data from the same Peruvian community showed that cryptosporidiosis without diarrhea had a substantial effect on childhood growth (21,22); because such infections may have long-term sequelae it is somewhat misleading to call them asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, serologic data suggest that even intensive stool surveillance may miss a substantial proportion of cryptosporidiosis episodes (20). Data from the same Peruvian community showed that cryptosporidiosis without diarrhea had a substantial effect on childhood growth (21,22); because such infections may have long-term sequelae it is somewhat misleading to call them asymptomatic.…”
Section: Discussionmentioning
confidence: 99%
“…Diarrhea caused by these parasites in early childhood has been associated with subsequent cognitive function deficits and growth faltering and stunting, and the risk of stunting increases with the number of episodes per year. [1][2][3][4][5][6] A study from Peru found that symptomatic and asymptomatic cryptosporidiosis in children were associated with growth faltering after an infection but recovery was slower in children with symptomatic infection. 7 In India, several studies have reported Cryptosporidium spp.…”
Section: Introductionmentioning
confidence: 99%
“…In immunocompetent individuals, Cryptosporidium infection causes watery diarrhea, often continuing beyond 10 days from the onset [7]. Cryptosporidium is a major cause of diarrhea in children in developing countries and is associated with stunting, irreversibly impaired cognitive development, and decreased fitness [9][10][11]. With improved diagnostic data from the Global Enteric Multicenter Study (GEMS), Cryptosporidium infections are now linked to approximately 25% of moderate-to-severe diarrheal episodes in children aged <2 years in resource-limited countries, second only to rotavirus [3].…”
mentioning
confidence: 99%